(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The thesis examines the characteristics, organizational structure, financing sources, and coverage level of the health insurance system of the People’s Republic of China. It analyzes China’s experience in reforming its compulsory health insurance system. Special attention is given to the potential adaptation of certain elements of the Chinese model within the context of Uzbekistan, particularly regarding the digitalization of insurance services, the implementation of a family doctor system, and the development of national mechanisms for quality control of medical care.